2018
DOI: 10.1111/aab.12476
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of bacterial plant diseases with Lactobacillus plantarum strains selected for their broad‐spectrum activity

Abstract: The use of lactic acid bacteria (LAB) to control multiple pathogens that affect different crops was studied, namely, Pseudomonas syringae pv. actinidiae in kiwifruit, Xanthomonas arboricola pv. pruni in Prunus and Xanthomonas fragariae in strawberry. A screening procedure based on in vitro and in planta assays of the three bacterial pathogens was successful in selecting potential LAB strains as biological control agents. The antagonistic activity of 55 strains was first tested in vitro and the strains Lactobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(61 citation statements)
references
References 58 publications
1
60
0
Order By: Relevance
“…The bacteria were able to live on the leaves at the concentration of about 10 4 CFU per leaf. The test strains reduced disease incidence from 40% to 10-12% (Daranas et al 2018).…”
Section: Lab: Lactic Acid Bacteriamentioning
confidence: 95%
“…The bacteria were able to live on the leaves at the concentration of about 10 4 CFU per leaf. The test strains reduced disease incidence from 40% to 10-12% (Daranas et al 2018).…”
Section: Lab: Lactic Acid Bacteriamentioning
confidence: 95%
“…Indeed, many Bacillus and Streptomyces strains have been shown to have a broad range biocontrol effect (Shafi, Tian and Ji 2017;Vurukonda, Giovanardi and Stefani 2018) and several have been commercialised (Table 2). Numerous studies have demonstrated that foliar treatment with commercial or naturally isolated bacilli and Streptomyces strains significantly reduced Xanthomonas caused diseases in multiple crops in field trials (Van Hop et al 2014;Thapa and Babadoost 2016;Daranas et al 2019).…”
Section: Biocontrol Through Beneficial Microorganismsmentioning
confidence: 99%
“…In contrast, Wei et al (2016) found that the relative abundance of a potential BCA (Bacillus subtilis) in strawberry leaves was found to be depleted by 50% 8 days post-inoculation under field conditions. Another study found the population size of a potential Lactobacillus plantarum BCA decreased significantly 10 days after inoculation on kiwifruit, strawberry, and Prunus leaves, even under stable greenhouse conditions (Daranas et al, 2019). When compared to those BCAs, which were isolated from plants or soil, our rain-borne isolate BAV2934 demonstrated better survival on aerial plant surfaces.…”
Section: Contigmentioning
confidence: 72%
“…However, since differences in bacterial survival rate depend on the type of plant surface (Pujol et al, 2006;Bonaterra et al, 2007) and environmental conditions (Nuclo et al, 1998), we cannot make general conclusions before testing our rain-isolated bacteria in different geographic locations. Some BCAs have a broad spectrum of inhibition against many plant pathogens (Ishimaru et al, 1988;Mora et al, 2015;Daranas et al, 2019). Here, we observed that our initial 9 rain-isolated bacteria have the ability to suppress a wide range of bacterial, fungal, and oomycetes pathogens in vitro ( Supplementary Table S2).…”
Section: Contigmentioning
confidence: 83%